Competency-Based Human Resources (HR) Development in the Digital Era - Septiadi, Muhammad Andi; Ramdani, Zulmi (UIN Sunan Gunung Djati Bandung, 2024)
The increasingly tight global market competition requires organizations to improve their competitiveness through competency-based human resource (HR) development. This approach focuses not only on technical training, but also on the development of interpersonal skills, leadership, and adaptability. This article analyzes the implementation strategies and challenges in competency-based HR development using qualitative research methods and explores case studies to illustrate the positive impact of this approach. Qualitative research was conducted through in-depth data analysis from various organizations and previous studies that have implemented competency-based HR development. The results show benefits such as increased employee performance, organizational adaptability to change, and employee motivation and satisfaction. Digital technologies such as e-learning and virtual simulations expand the scope and effectiveness of competency development programs. Case studies and qualitative data show that organizations that successfully implement this approach can achieve competitive advantage and sustainable growth. However, challenges such as identifying relevant competencies, implementing effective training programs, and data security still need to be addressed. With a well-planned strategy and the right technology integration, organizations can optimize the potential of competency-based HR development to achieve competitive advantage and sustainable growth. This article provides a contribution in the form of an analysis of implementation strategies, challenges, and the use of digital technology in competency development programs, as well as providing relevant case studies and qualitative data, so that it is expected to be a reference for organizations that want to implement this approach.